EFFECTIVE PRINCIPAL LEADERSHIP (SBM IMPLEMENTATION) - Nurhasanah HS; Juriah Juriah; Muhamad Yusup; Riyan Fatukaloba; Nur Afif (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
An ideal school reflects harmony between student achievement and the targets set. Effective schools are not only filled with students with high learning abilities who are able to develop, but also with students with average intellectual abilities who may not have reached their maximum potential. In this context, the role of the school principal is very crucial in ensuring school effectiveness. A school principal plays a vital role in the education system of every institution. School principals are indispensable in implementing school-centered management, an approach that emerged as a result of decentralization in the reform era. School-centered management policies give educational institutions the freedom to manage all available resources. This freedom is a responsibility carried out by the principal to advance the school he leads.